2017
DOI: 10.14309/crj.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine-Induced Hepatotoxicity

Abstract: Drug-induced injury (DILI) is a frequent cause of abnormal liver tests and a leading cause of liver failure in the United States. Colchicine has long been used as a systemic anti-inflammatory agent for treatment of gout by inhibiting mitotic activity and neutrophil function. We present the first case of colchicine-induced hepatoxicity, supported by histopathologic findings characteristic of colchicine-induced injury and resolution of liver enzyme abnormalities after its discontinuation. Colchicine-associated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
1
16
1
5
Order By: Relevance
“…This morphological report was compatible with steatohepatitis ( Figure 1 ). However, these results were not consistent with colchicine-induced liver injury, which occurs in cases of drug overdose, characterized by typical histopathological elements, i.e., anisonucleosis with enlarged nuclei, multiple nucleoli and frequent mitotic figures arrested in metaphase 23 , which were not present.…”
Section: Case Reportcontrasting
confidence: 65%
See 1 more Smart Citation
“…This morphological report was compatible with steatohepatitis ( Figure 1 ). However, these results were not consistent with colchicine-induced liver injury, which occurs in cases of drug overdose, characterized by typical histopathological elements, i.e., anisonucleosis with enlarged nuclei, multiple nucleoli and frequent mitotic figures arrested in metaphase 23 , which were not present.…”
Section: Case Reportcontrasting
confidence: 65%
“… 38 Colchicine has a narrow therapeutic range, and hepatotoxicity as a possible consequence of long-term administration has been shown. 23 In fact, colchicine intoxication with daily doses higher than 5 mg might determine liver toxicity. 13 , 38 Of note, the usual doses used to prevent FMF attacks do not seem to bring about a significant increase in liver enzymes in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is a controversy around hepatotoxicity after colchicine treatment. Experimental studies have shown that colchicine causes hepatotoxicity, including acute hepatic necrosis and steatosis in animals [9,27]. Guo X. et al reported that CYP3A inhibition was associated with colchicineinduced hepatotoxicity in animals [28].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that colchicine is associated with a risk of hepatotoxicity in gout patients prescribed febuxostat [8], which has also been reported to induce acute liver injury [9]. However, there are few studies regarding hepatic safety of colchicine as a prophylactic therapy in gout patients treated with febuxostat.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine is the treatment currently used to inhibit hepatocellular secretion of collagen and stop fibrotic tissue production. Its efficacy has not been yet confirmed due to its severe adverse effects [3, 4]. The lack of an effective therapy to prevent progression of liver damage has generated several lines of research including the search for compounds with hepatoprotective activity.…”
Section: Introductionmentioning
confidence: 99%